The Impact of Reflective Practice on Developing Pedagogical Skills for Future Islamic Education Teachers in Islamic Higher Education - Maskur; Mashuri (Barkah Publishing, 2024)
Reflective practice has become more and more important in the professional development of lecturers especially in Islamic education. This study aims to look into how Islamic education lecturers engage with reflective practices and how these practices contribute to their professional expertise and spiritual growth. Using mixed-methods approach, the research combines quantitative data from 100 Islamic education students with qualitative insights from lecturers. The findings show that reflective practices such as journaling, self-assessment and peer discussion are widely seen as useful tools to improve teaching effectiveness. However, practical challenges such as heavy workloads and lack of institutional support impede the implementation of these practices. The study also highlights the duality of reflection in Islamic education context where professional growth is intertwined with spiritual values. Practices rooted in ilm (knowledge) and tazkiyah (self-purification) not only enhance pedagogical skills but also deepen sense of purpose in teaching. To address these challenges, the study suggests the Holistic Reflective Integration Model (HRIM). This framework encompasses professional, ethical and spiritual dimensions of reflective practice. HRIM stresses the need for strong institutional support to make reflective practices effective and sustainable. By using this model, Islamic education institutions can create an environment that fosters both professional and spiritual growth of lecturers.